Kilka uwag o potrzebie badań kompetencji słowotwórczych dzieci z niepełnosprawnością intelektualną w stopniu lekkim - Marciniak-Firadza, Renata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Word formation is significant for the linguistic and cognitive development of the child and it is possible to get and interpret data concerning decoding and encoding word-formative structures by children with intellectual disability through linguistic analysis. This task is so much important because Polish literature lacks studies concerning word formation competence of children with intellectual disability. The article shows the need for research and their description as well as the evaluation of understanding and forming word-formative structures by children with intellectual disability in comparison with analogical abilities of children without such a disability.